USING PARE FRUIT (Momordica charantia L) AS AN ANTIDEPRESSANT AGENT USING THE FORCED SWIM TEST (FST) METHOD: PARE FRUIT (Momordica charantia L) AS AN ANTIDEPRESSANT AGENT USING THE FORCED SWIM TEST (FST) METHOD - Suzana, Dona; Kencana, Ghista Kurnia (JFL : Jurnal Farmasi Lampung, 2025)
Depression is a serious psychological disorder that requires long-term therapy. The use of synthetic antidepressants such as fluoxetine often causes side effects and complex drug interactions, thus encouraging the search for herbal alternatives. This study evaluated the antidepressant activity of ethanol extract of bitter melon fruit (Momordica charantia L.) through the Forced Swim Test (FST) method in male Balb/c mice. Four treatment groups were used: negative control (aquadest), positive control (fluoxetine 120 mg/kgBB), comparative control (stelazine), and bitter melon extract (270 mg/kgBB). The results of the FST test showed that bitter melon extract significantly reduced the immobility time of mice (p = 0.005), equivalent to fluoxetine and stelazine. Phytochemical tests identified the presence of flavonoids, triterpenoids, alkaloids, saponins, and polyphenols, which are thought to contribute to antidepressant activity through increased monoamine levels and neuroprotective effects. The conclusion is that ethanol extract of bitter melon shows strong potential as an herbal antidepressant agent comparable to fluoxetine, as well as being feasible to be developed as a phytopharmaceutical for depression therapy. Keywords: bitter melon, antidepressant, Momordica charantia, Forced Swim Test, triterpenoids